(untitled) (Passagens: Revista Internacional de História Política e Cultura Jurídica, 2022)
The intrinsic importance and value of geographical indications and their special characteristics, which, if protected, would have far-reaching economic, cultural and even political benefits, would justify the need to protect them. The present study descriptively-analytically examined the legal protection of geographical indications nationally and internationally and identified gaps in the protection of signs in Iranian law. The results showed that recognizing a geographical indication, whether through registration, court, administrative decision or other means, is not sufficient to realize the potential benefits of protecting a geographical indication. Also, although protecting a geographical indication is essential, it is not the only condition for its success. Also, although there are several ways to protect a geographical indication in theory, even ancillary laws such as the "Fight against Unfair Competition" and the "Consumer Protection Act" and other similar rules and regulations are among these valuable intellectual assets. They protect. However, there are limitations to their protection in practice, largely due to the wide variety of protection systems associated with these symptoms. It was also observed that despite special rules in some countries and territories with geographical indications, including Iran, there is still no global consensus and a single legal authority to support these indications at the international level fully. Therefore, it is necessary to create a comprehensive geographical indication design for a geographical indication to effectively create brand equity for a product or positively impact rural development or the preservation of traditional knowledge, traditional cultural expressions, or biodiversity.